2021
DOI: 10.1371/journal.pone.0250440
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of Alzheimer’s disease among patients with age-related macular degeneration: A nationwide population-based study

Abstract: Objective This study aimed to investigate the risk of Alzheimer’s disease among patients with age-related macular degeneration and its association with confounding comorbidities. Method This was a population-based, retrospective cohort study. By accessing data from the National Health Insurance Research Database of Taiwan, we identified 10,578 patients aged 50–100 years who were newly diagnosed with age-related macular degeneration between 2000 and 2012 and 10,578 non- age-related macular degeneration indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…17 Previous studies using health administrative records have reported associations between glaucoma/AMD and Alzheimer's disease or dementia. [18][19][20][21] Few studies have been conducted on cataract and cognition. One previous study found that cognitive decline was slower after cataract surgery than before it 48 although a randomized controlled trial found no cognitive benefit to cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Previous studies using health administrative records have reported associations between glaucoma/AMD and Alzheimer's disease or dementia. [18][19][20][21] Few studies have been conducted on cataract and cognition. One previous study found that cognitive decline was slower after cataract surgery than before it 48 although a randomized controlled trial found no cognitive benefit to cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, very few clinical studies have examined the relationship between eye disease and cognitive function. 16,17 Studies on eye disease, instead, have often used health administrative records and have focused on outcomes like Alzheimer's disease or dementia reporting positive relationships in some cases [18][19][20][21] and null findings in others. 22 Prior studies have also neglected to examine potential effect modifiers such as sex, education, or hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Earlystage AMD features the emergence of drusen and RPE degeneration, while late-stage AMD features geographic atrophy and choroidal neovascularization [144]. Some studies suggest that AMD and AD might be comorbid by showing that patients with AMD have an increased risk of AD [145][146][147], although this correlation becomes not significant when considering other factors such as age, presence of the apolipoprotein E (ApoE) allele, smoking, and atherosclerosis [145,148]. Evidence that Aβ deposition is involved in chronic inflammation, oxidative stress, and neuronal damage in both AD and AMD, suggests that the pathological similarities between these diseases, to some extent, may reduce the specificity of potential biomarkers for AD diagnosis [149].…”
Section: Retinal Dysfunction In Age-related Macular Degenerationmentioning
confidence: 99%
“…Besides, hypercholesterolemia, hypertension, atherosclerosis, obesity, diabetes, and environmental risk factors also strongly contribute to the development of both AD and AMD in midlife (Kivipelto et al, 2001(Kivipelto et al, , 2002(Kivipelto et al, , 2005Newman et al, 2005;Polidori et al, 2001;Seddon et al, 2005; Age-Related Eye Disease Study Research Group (AREDSRG), 2000; Kaarniranta et al, 2011;Ohno-Matsui, 2011). Relevantly, patients suffering AMD exhibit an increased risk of developing AD as compared with people without AMD (Frost et al, 2016;Wen et al, 2021), even though a direct association between these two disorders has not been confirmed (Williams et al, 2014). Besides, compelling studies have demonstrated that vision abnormalities featured by degeneration of the visual cortex and/or RGC loss or AMD-like retinal degeneration are prominent in AD patients and manifest even before clinical signs of cognitive decline (Ashok et al, 2020).…”
Section: Alzheimer's Disease and Amd Pathophysiology: Similarities And Differencesmentioning
confidence: 99%